STRATEGIC MANAGEMENT OF SMK MIGAS CEPU AS A VOCATIONAL SCHOOL CENTER OF EXCELLENCE - Mulyono; Nurkolis; Ngurah Ayu Nyoman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study explores the management practices at SMK Migas Cepu as a Vocational School Center of Excellence (SMK-PK), focusing on the four key management functions: planning, organizing, implementing, and controlling. The research highlights the role of participatory planning, which involves collaboration with both internal and external stakeholders, including industry partners, in developing the curriculum and other educational strategies. Organizing at SMK Migas Cepu follows a systematic approach, with clear divisions of responsibilities and coordination among teachers, staff, and industry partners. The implementation of the SMK-PK program includes project-based learning, industrial internships, guest lectures from industry professionals, and certifications, all aimed at aligning the curriculum with industry needs and improving the employability of students. The controlling function ensures quality management through regular monitoring and evaluation of processes. The findings suggest that the school’s effective management practices have significantly contributed to its success as an SMK-PK, although challenges remain in areas such as data-driven monitoring, continuous teacher training, and optimizing partnerships with industry. The study concludes with recommendations to further enhance the program’s sustainability and improve the competitiveness of its graduates